2007
DOI: 10.1093/nar/gkm322
|View full text |Cite
|
Sign up to set email alerts
|

KinasePhos 2.0: a web server for identifying protein kinase-specific phosphorylation sites based on sequences and coupling patterns

Abstract: Due to the importance of protein phosphorylation in cellular control, many researches are undertaken to predict the kinase-specific phosphorylation sites. Referred to our previous work, KinasePhos 1.0, incorporated profile hidden Markov model (HMM) with flanking residues of the kinase-specific phosphorylation sites. Herein, a new web server, KinasePhos 2.0, incorporates support vector machines (SVM) with the protein sequence profile and protein coupling pattern, which is a novel feature used for identifying ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
267
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 322 publications
(267 citation statements)
references
References 23 publications
0
267
0
Order By: Relevance
“…For example, DBN-1 is a possible target for phosphorylation by Src-1 (ref. 38). Association of DBN-1 and LEV-11 with distinct parts of actin filaments at muscle contraction suggests that DBN-1 and tropomyosin compete for the binding to F-actin.…”
Section: Discussionmentioning
confidence: 99%
“…For example, DBN-1 is a possible target for phosphorylation by Src-1 (ref. 38). Association of DBN-1 and LEV-11 with distinct parts of actin filaments at muscle contraction suggests that DBN-1 and tropomyosin compete for the binding to F-actin.…”
Section: Discussionmentioning
confidence: 99%
“…The SNP4 mutation leads to a substitution of serine for proline at position 365 in the predicted C-terminal fibrinogen-like domain. The KinasePhos 2.0 web server was used to predict phosphorylation sites of the ANGPTL3 (Wong et al, 2007). The result showed that serine-365 (S365) is a potential phosphorylation site.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted to the same number of phosphorylated virus proteins from virPTM, 12 phosphorylated proteins with 24 pSer, and 10 pThr from UniProtKB as well as 4 phosphorylated proteins with 2 pSer, and 2 pTyr from Phospho.ELM. In order to investigate the surrounding amino acids composition, with reference to KinasePhos [10], [11], sequence fragments are extracted using a window size of 11 centered on the phosphorylated residue. Fragments centered on phosphorylated residues are obtained and regarded as positive data while fragments centered on non-phosphorylated residues are regarded as negative data.…”
Section: A Data Constructionmentioning
confidence: 99%
“…This is done in order to avoid a biased prediction performance. With reference to previous phosphorylation prediction methods [10], [12]- [15], a smaller number of negative fragments are obtained to match the number of positive fragments. This resulted to an equal number of positive and negative S, T, and Y fragments respectively in the three data sets as shown in Table I.…”
Section: A Data Constructionmentioning
confidence: 99%
See 1 more Smart Citation